Keterampilan Individu Mahasiswa Indonesia dalam Menghadapi Risiko dan Peluang Digital Melalui Pendekatan Confirmatory Factor Analysis (CFA) - Hery Sawiji; Subroto Rapih; Yosep Tegar Prameswara (Jurnal Ilmu Sosial dan Humaniora, 2024)
Discussions about the risks and opportunities of youngsters accessing digital media need to take place in the current era of hyper-globalization. Prior studies suggest that enhancing teenagers' fundamental skills is the most effective approach to enhance internet possibilities and mitigate online risks. This project aims to assess computational thinking skills, critical thinking skills, and communication skills in relation to enhancing online possibilities and mitigating online risks. The second goal is to confirm the predicted characteristics that impact students' online danger and online opportunity through the PLS-SEM analytic method. 356 students participated in the survey. The research confirms that critical thinking and communication abilities can decrease online danger, however computational thinking skills do not impact online risk. The research findings successfully predicted that computational thinking skills, critical thinking skills, and communication skills positively impacted online opportunities. Students can mitigate online dangers when accessing digital media by employing critical thinking and communication skills, as indicated by the findings of this research. Students must enhance their fundamental skills including computational thinking, critical thinking, and communication to maximise online prospects.